Specific Claims in Canada: Status Report - Indian and Northern Affairs Canada (Creator) (Government of Canada, 1985)
Glossary of Abbreviations ii Claims Listed by Province and Alphabetically Nova Scotia 1 New Brunswick 2 Quebec 3 Ontario 5 Manitoba 11 Saskatchewan 11 Alberta 13 British Columbia 15 Yukon 20 A summary of land claims made by First Nations tribes, the content of their claims, and the status of those claims at the time of publication